LITERATURE REVIEW TENTANG SEJARAH PERANG DALAM STRATEGI PERANG SEMESTA INDONESIA - Nanto Nurhuda (Sekolah Tinggi Pariwisata Mataram, 2021)
In a social community, conflict is inevitable. This is due to the interests of certain groups or individuals in a community who have an ego or desire to fulfill the needs of themselves or their groups. In an effort to fulfill this ego or desire it can result in friction with other individuals or groups. The factor of natural resources in meeting industrial needs and raw materials is one of the limitations driving conflicts between countries. Various conflicts between countries occur in the context of seizing territory and natural resources. Various war strategies have also been applied in order to win with the best possible results and very small losses. Several war leaders became a reference in the implementation of the next war. We know war strategy figures such as Napoleon, Mao Ze Dong, Guevara, and war leaders from within the country such as Cik Di Tiro, Imam Bonjol, Cut Nya' Dien, Diponegoro, Jenderal Sudirman, also A.H. Nasution. These figures are the reference and inspiration in formulating the Indonesian nation's war strategy so that determining the people's war strategy is the best choice for the Indonesian nation.